Financial aid at private universities in the Middle East : its impact on persistence and student satisfaction, the case of Lebanon - Nasser, Ramzi N. (2009)
Many private universities around the world sustain their growth and retain students through a system of ‘cost-sharing’ where fees and tuition are channelled back to students in form of financial aid. Not all students are successful in obtaining financial aid solely based on need, but are also awarded aid based on their academic performance. This study questions whether a combination of financial aid types has a positive impact on graduating from a private university in Lebanon. Furthermore, this study assesses students’ satisfaction with the university at large by comparing those who received a combination of financial aid with those who applied and were not granted financial aid. Findings illustrate that the frequency and amount of financial aid received by students produced greater graduation percentages. In addition, no difference appeared between graduates and those who did not complete degree requirement regarding their satisfaction with university services and programmes.